Equivalent axisymmetric plasma response models of EAST. (20th January 2016) - Chen, S L; Villone, F; Xiao, B J; Barbato, L; Mastrostefano, S; Luo, Z P; Guo, Y; Liu, L
Abstract: A strategy is presented for the derivation of simplified equivalent axisymmetric models of vertical instabilities in the EAST tokamak device. The qualitative understanding and the quantitative results obtained from a 3D model can suggest and quantify suitable modifications of the axisymmetric structures in order to fit both the growth rate and the stability margin for a wide range of different experimental configurations.